Design, fabrication & testing of water channel - Loh, Chong Sean (2013)
Fossil fuel generates most of the energy in Malaysia. However, oil and gas in Malaysia are depleting now. Government of Malaysia has been identified renewable energy as fifth fuel under New Five-Fuel Diversification Strategy. Tidal energy is a renewable energy, which is also pollutant free, predictable, and has huge energy density. The scene of tidal energy extraction can be investigated through small-scale model using a water channel. In order to simulate tidal energy extraction, dimensional analysis method is used when designing the water channel. Pump of maximum flow rate0.0125m3 /s at 2m head is used. After fabrication, the water channel is tested to ensure it fulfill the design requirement. The vertical velocity profiles are also investigated by current meter and compare to the vertical velocity profiles of real tidal field. After testing, the water channel shows that it approaches the vertical velocity profiles of real tidal field at certain flow rate.